DnaA protein is required for replication of the minimal replicon of the broad-host-range plasmid RK2 in Escherichia coli. - Gaylo, P J (1987)
The minimal origin of replication of the broad-host-range plasmid RK2 has two potential recognition sequences for the DnaA protein of Escherichia coli. DNA transfer by transformation into a dnaA-null mutant of E. coli showed that DnaA protein is needed for replication or maintenance of mini-RK2. We isolated and purified DnaA protein as a chimeric protein, covalently attached to a piece of collagen and beta-galactosidase. The hybrid protein specifically bound to restriction fragments from the oriV region of RK2, which contained the two dnaA boxes. Deletion of the second dnaA box inactivated the origin and abolished the binding of the hybrid protein to the DNA fragment that had suffered the deletion. When the second dnaA box was replaced with an EcoRI linker of identical length, origin activity was restored. Binding experiments showed that the linker provided a weak dnaA box. An alternative explanation was that the linker restored proper spacing between sequences on either side of the deleted box, thus restoring origin activity.